2018
DOI: 10.1177/1099636218783328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt water exposure on foam-cored polyurethane sandwich composites

Abstract: This study investigated the effect of moisture absorption on the mechanical performance of polyurethane sandwich composites. The core material was a closed cell polyurethane foam. Face sheets were made of E-glass/polyurethane composite laminates. Vacuum-assisted resin transfer molding process was used to manufacture specimens for testing. The foam core, laminates, and sandwich composites were submerged in salt water for prolonged periods of time. Mechanical property degradation due to moisture absorption for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The pure PU foam was prepared by Caglayan et al, [ 12 ] and its compressive strength was 0.88 MPa. Huo et al [ 3 ] prepared a closed cell PU foam, and its compressive strength was 994.5 kPa. By comparison, the compression strength of a foaming agent of 2% was 4.16 MPa and increased by 372.7%, 318.3%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pure PU foam was prepared by Caglayan et al, [ 12 ] and its compressive strength was 0.88 MPa. Huo et al [ 3 ] prepared a closed cell PU foam, and its compressive strength was 994.5 kPa. By comparison, the compression strength of a foaming agent of 2% was 4.16 MPa and increased by 372.7%, 318.3%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This is of great significance for the preparation of PU foam as core materials and fiber reinforced PU composites as surface layer with excellent properties. [3][4][5] The sandwich-structure panel is usually composed of top and bottom panels with high strength and stiffness and a light mass-large volume core layer, thus has excellent lightweight, high strength, and some other special functions. For the PU sandwich-structure panel, the upper and lower surface panel materials are usually metal or fiber reinforced composite panel, [6,7] and the core layer is PU-based material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known the chloride diffusion will cause damages to various materials [72,73]. Huo et al [74] investigated the mechanical property of closed cell polyurethane foam immersed in salt water and the experimental results indicated that the flexural modulus and strength decreased by 8.9% and 13%, respectively, after 150 days of exposure to salt water. Saharudin et al [75] tested halloysite nanotubes-polyester nanocomposites and found that the storage modulus, tensile properties and flexural properties of polyester and its nanocomposites decreased after seawater exposure.…”
Section: Introductionmentioning
confidence: 99%